E-152 Seimless: simultaneous extracranial, intracranial management of (TANDEM) lessions in stroke. (22nd July 2018) - Sultan-Qurraie, A; Witt, T; Havenon, A de; Lin, E; Zaidat, O
Abstract : Background: Pooled individual data from the landmark stroke trials of 2015 concludes that the benefit of endovascular thrombectomy for patients with intracranial arterial occlusion also extends to patients with concomitant (so-called 'tandem') occlusions of proximal vessels. However, there is heterogeneity and debate in the management of these patients, without a clear standard of care. In particular, there is contention regarding whether the proximal or distal lesion should be treated first. We present a case-control study and describe the 'SEIMLESS' technique, an efficient approach to the acute ischemic stroke (AIS) patient who presents with tandem lesions (TLs). Methods: We describe five patients, presenting with AIS and TLs between 2015 and 2017, who we treated with SEIMLESS. Cases were reviewed for variables including arterial puncture to intracranial reperfusion, total fluoroscopy time, amount of contrast, age, and gender. Our series was matched to five patients treated with the standard 'sequential' approach in the same time period by the same operator. To compare intergroup differences, we used Student's t-test, which has been shown to be robust to a small sample size. Results: Arterial access to intracranial recanalization time was significantly longer in the patients who had angioplasty followed by thrombectomy versus patients who were treated by SEIMLESS (79±25 min versus 40±6 min, p=0.009). Patients treated 'seimlessly' also received significantly less iodinated contrast (117±14 mL versus 213±58 mL, p=0.007) and significantly less fluoro time (21±5 min versus 52±22 min, p=0.013). Conclusion: SEIMLESS is an efficient procedural method that simultaneously treats a distal intracranial occlusion and a more proximal one. Our small case-controlled study finds that this technique is feasible and can lead to faster intracranial recanalization compared with the standard 'sequential' method, utilizing less contrast and radiation in the process. Larger studies are needed to verify our findings. Disclosures: A. Sultan-Qurraie: None. T. Witt: None. A. de Havenon: None. E. Lin: None. O. Zaidat: None.